2000
DOI: 10.1038/sj.mp.4000688
|View full text |Cite
|
Sign up to set email alerts
|

Genomic structure and novel variants of myo-inositol monophosphatase 2 (IMPA2)

Abstract: Recently, we cloned the human myo-inositol monophosphatase 2 (IMPA2) cDNA and established its map location to chromosome 18p11.2, a region previously implicated in bipolar disorder. Because the myo-inositol monophosphatase enzyme has been shown to be inhibited by lithium, an effective therapeutic agent for bipolar disorder, IMPA2 is a plausible positional and functional candidate gene. To permit comprehensive screening for variants we characterized the genomic structure and isolated the potential promoter of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 16 publications
0
43
0
1
Order By: Relevance
“…The interpretation of the inositol depletion hypothesis has been complicated further by the discovery of a second gene coding for IMPase named IMPA2 (Sjoholt et al, 2000;Yoshikawa et al, 2000). IMPA2 is located on chromosome 18 near a region implicated in linkage studies of manic depressive illness (Berrettini et al, 1994;Rojas et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The interpretation of the inositol depletion hypothesis has been complicated further by the discovery of a second gene coding for IMPase named IMPA2 (Sjoholt et al, 2000;Yoshikawa et al, 2000). IMPA2 is located on chromosome 18 near a region implicated in linkage studies of manic depressive illness (Berrettini et al, 1994;Rojas et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A number of candidate genes on chromosome 18p11 have been investigated for association with genetic markers, including NAPG, PACAP, MC5R, IMPA2, NDUFV2, GNAL and CLUL1 [13][14][15][16][17][18][19][20][21] (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…The gene has been mapped to chromosome 18p11.2 10 and its structure has been characterized. 11,12 The gene is a potential biochemical target for the action of lithium. 13 Linkage studies 14,15 have suggested the presence of a susceptibility locus for bipolar disorder on chromosome 18p11.2.…”
Section: Introductionmentioning
confidence: 99%
“…13 Linkage studies 14,15 have suggested the presence of a susceptibility locus for bipolar disorder on chromosome 18p11.2. The gene has been screened for polymorphisms and tested for association with BP 11,12 and schizophrenia. 16 Yoshikawa et al 12 described only three polymorphisms: 97À15G4A, 159T4C and 226C4T (His76Tyr), and tested their frequencies in 96 BP individuals and 59 unrelated persons from CEPH families.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation